Análise de marcadores químicos do produto fitoterápico Dermodilapiol (Piper aduncum) - Oliveira, Laura Cristina Pereira de (2005)
This work describes the isolation and structure elucidation of two phenylpropanoids (dillapiol and myristicin), one prenylated benzoic acid derivative (methyl 4-hydroxy-3-(3-methyl-2-butenyl)-benzoate), one chalcone (dihydroflavokawin B) and one flavanone (sakuranetin) from the phytoterapeutical product Dermodilapiol, produced from the aerial parts of Piper aduncum. The isolation of the chemical markers has been done from its active fraction, obtained from a liquid-liquid partition and further chromatographic steps. Four different lots of the product have been analysed by high performance liquid chromatography using two different methods. A longer method was used to describe the chromatographic profiles of each lot and a shorter method was used to quantify two of the chemical markers in the product. In both cases, it could be observed a correlation between the chemical composition and biological activity. It has also been studied the essential oil production of leaves of P. aduncum collected in three different places in Manaus for a period of one year. During this period, dillapiol has always been the major component. A small chemical variability was observed to all specimens studied and apparently was correlated to the rainy season of the city.